(untitled) (American International Journal of Biology and Life Sciences, 2020)
To analyze the reasons for the extinction of dinosaurs by applying the elimination methods, to exclude the factors that could not cause the worldwide extinction of the dinosaurs. At last obtain a conclusion that because the Ice Age had come on the Earth and caused the changing of climate that it had been becoming cold and arid from warmth and moist, and caused the phyto-group had been changing, which the Pteridophyte and gymnosperm groups fell off or died out, but the angiosperm groups had been developing and expanding. The characters of photosynthesis of producers of the biosphere had been becoming to the seasonal and regional from the perennial and global, the total of oxygen had reduced sharply in the atmosphere, the density of oxygen had declined, and finally affected the breath of dinosaurs, and led to the extinction of dinosaurs. And as the main producers of biosphere, the pteridophyte and gymnosperm groups had fallen off or died out were the mainly reasons for the creature’s extinction at the later of the Cretaceous period.